Peta Maqashid Asy-Syariah dalam Hermeneutika Kontekstual Abid Al Jabiri - Barir, Muhammad (Rausyan Fikri Journal of Islamic Studies, 2023)
AbstractThis research focuses on the views of Abid Al Jabiri, a 20th century scholar who reconstructed the concept of contextualizing the Qur'an as a holy book that is tied to historical reality. The use of "Arabic" shows that the meaning of the Qur'an is directly proportional to the socio-cultural conditions of the Arab nation so that the Qur'an in turn can be understood differently when it is received in the context of a different place and time. Departing from this, this research aims to reveal Al Jabiri's contextual hermeneutics in tracing the contextual meaning of the Qur'an with three stages, namely Al Fashl, Al Washl, and Ashalatun Nash. The first is Al Fashl, which is letting the Qur'an speak to itself by separating the context and pre-knowledge of the interpreter, then Al Washl, which is connecting or reconnecting the meaning with the context and pre-knowledge of the interpreter, and the third is Ashalah An Nash, which is producing meaning from the original text. by integrating (appropriation) between the two previous stages holistically. The concept of Al Jabiri's contextual hermeneutic thinking on the message and position of revelation becomes the basis for how the interpretation of the Qur'an becomes more relevant to determining the map of maqashid ash shariaPenelitian ini berfokus pada pandangan Abid Al Jabiri, seorang cendekiawan abad ke-20 yang melakukan konstruksi ulang konsep kontekstualisasi Al Qur’an sebagai kitab suci yang terikat dengan kenyataan sejarah. Penggunaan “Bahasa Arab” menunjukkan bahwa makna Al Qur’an berbanding lurus dengan kondisi sosial budaya Bangsa Arab sehingga Al Qur’an pada gilirannya dapat difahami secara berbeda saat ia diterima dalam konteks tempat dan waktu yang berbeda pula. Berangkat dari hal tersebut, riset ini bertujuan untuk mengungkap peta Maqashid Asy Syariah dalam hermeneutika kontekstual Al Jabiri. Melalui penelusuran makna kontekstual Al Qur’an dengan tiga tahapan, yakni Al Fashl, Al Washl, dan Ashalatun Nash. Pertama adalah Al Fashl yakni membiarkan Al Qur’an berbicara dengan dirinya sendiri dengan memisahkan konteks dan pra pengetahuan penafsir, kemudian Al Washl yakni menghubungkan atau menyambungkan kembali makna dengan konteks dan pra pengetahuan penafsir, dan ketiga adalah Ashalah An Nash yakni menghasilkan makna dari nash asli dengan menyaturekatkan (appropriation) antara kedua tahapan sebelumnya secara holistik. Konsep berfikir hermeneutika kontekstual Al Jabiri atas pesan dan posisi wahyu menjadi landasan bagaimana penafsiran Al Qur’an menjadi lebih relevan dengan menentukan peta maqashid asy syariah.